2002
DOI: 10.1038/sj.bjp.0704505
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heparin and related molecules on vascular permeability and neutrophil accumulation in rabbit skin

Abstract: 1 Unfractionated heparin (UH) has been shown to possess a wide range of properties which are potentially anti-in¯ammatory. Many of these studies, including eects of heparin on adhesion of in¯ammatory cells to endothelium, have been carried out in vitro. In the present study, we have used radioisotopic techniques to study the eect of UH, and related molecules, on in vivo in¯ammatory responses (plasma exudation (PE) and PMN accumulation) in rabbit skin induced by cationic proteins, mediators and antigen. ) intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In the latter case, activated leukocytes are responsible for the plasma leakage because LTB 4 itself has no direct permeability-increasing activity on the endothelium [4]. The capacity of polyanions to antagonize neutrophildependent permeability responses in vivo has been confirmed in more recent studies [113]. However, in direct contrast to the aforementioned studies, opposite findings with regard to the effect of enzyme inhibitors and polyanions, respectively, have been obtained in a model for neutrophil-evoked permeability changes in cultured EC in vitro [102].…”
Section: Role Of Neutrophil Cationic Proteins In Regulation Of Endothmentioning
confidence: 93%
“…In the latter case, activated leukocytes are responsible for the plasma leakage because LTB 4 itself has no direct permeability-increasing activity on the endothelium [4]. The capacity of polyanions to antagonize neutrophildependent permeability responses in vivo has been confirmed in more recent studies [113]. However, in direct contrast to the aforementioned studies, opposite findings with regard to the effect of enzyme inhibitors and polyanions, respectively, have been obtained in a model for neutrophil-evoked permeability changes in cultured EC in vitro [102].…”
Section: Role Of Neutrophil Cationic Proteins In Regulation Of Endothmentioning
confidence: 93%
“…Pretreatment with heparin in animal models of inflammation has been shown to inhibit eosinophil infiltration into the lung (Sasaki et al, 1993;Seeds et al, 1993Seeds et al, , 1995 and skin in response to a range of inflammatory insults (Teixeira and Hellewell, 1993), neutrophil accumulation in the inflamed peritoneal cavity (Nelson et al, 1993;Lever et al, 2010), independently of anticoagulant activity (Lever et al, 2010), and vascular permeability in the skin (Carr, 1979;Jones et al, 2002). Furthermore, heparin has been shown to inhibit bronchial hyper-responsiveness in rabbits in response to platelet-activating factor (Sasaki et al, 1993); in sheep in response to inhaled allergen (Ahmed et al, 1992), an effect that was shared by very low molecular weight and non-anticoagulant heparins (Ahmed et al, 1997); and in guinea-pigs, in which the protective effect of heparin against airway hyper-responsiveness to methacholine was found to be attributable to preservation of nitric oxide signaling (Maarsingh et al, 2004).…”
Section: A Acute Inflammatory Reactionsmentioning
confidence: 99%
“…Heparin has been shown to have anti-inflammatory properties and it was reported that heparin as well as a 10 kDa dextran sulfate inhibited neutrophil activation, neutrophil accumulation and plasma leakage in the rabbit skin after i.v. injection (Brown et al, 2003, Jones et al, 2002). TNF-induced neutrophil accumulation and subsequent pulmonary edema was inhibited by an 8 kDa dextran sulfate and to a greater extent by dextran sulfate of 500 kDa (Höcking et al, 1991).…”
Section: Discussionmentioning
confidence: 99%